Polygenic score modifies risk for Alzheimer's disease in APOE ε4 homozygotes at phenotypic extremes. Issue 1 (5th August 2021) - Huq, Aamira J.; Fulton‐Howard, Brian; Riaz, Moeen; Laws, Simon; Sebra, Robert; Ryan, Joanne; ,; Renton, Alan E.; Goate, Alison M.; Masters, Colin L.; Storey, Elsdon; Shah, Raj C.; et al.
Abstract: Introduction: Diversity in cognition among apolipoprotein E ( APOE ) ε4 homozygotes can range from early‐onset Alzheimer's disease (AD) to a lifetime with no symptoms. Methods: We evaluated a phenotypic extreme polygenic risk score (PRS) for AD between cognitively healthy APOE ε4 homozygotes aged ≥75 years (n = 213) and early‐onset APOE ε4 homozygote AD cases aged ≤65 years (n = 223) as an explanation for this diversity. Results: The PRS for AD was significantly higher in APOE ε4 homozygote AD cases compared to older cognitively healthy APOE ε4/ε4 controls (odds ratio [OR] 8.39; confidence interval [CI] 2.0–35.2; P = .003). The difference in the same PRS between APOE ε3/ε3 extremes was not as significant (OR 3.13; CI 0.98–9.92; P = .053) despite similar numbers and power. There was no statistical difference in an educational attainment PRS between these age extreme case‐controls. Discussion: A PRS for AD contributes to modified cognitive expression of the APOE ε4/ε4 genotype at phenotypic extremes of risk.